Belly Up - Gibbs, Stuart (London Simon & Schuster Books Young Reader, 2011)
Twelve-year-old Teddy investigates when a popular Texas zoo's star attraction--Henry the hippopotamus--is murdered.
Keywords: Zoos -- Zoo animals -- Texas